A novel mutation in the glucose-6-phosphate dehydrogenase gene in a subject with chronic nonspherocytic hemolytic anemia—characterization of enzyme using yeast expression system and molecular modeling - Grabowska, Dorota; Jablonska-Skwiecinska, Ewa; Plochocka, Danuta; Chelstowska, Anna; Lewandowska, Irmina; Witos, Iwona; Majewska, Zofia; Rokicka-Milewska, Roma; Burzynska, Beata (Blood cells, molecules, & diseases, 2004)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzymopathy. Human G6PD gene is highly polymorphic, with over 130 mutations identified, many of which cause hemolytic anemia. We studied a novel point mutation in the G6PD gene 1226 C→G, predicting the proline 409 to arginine substitution (G6PD Suwalki). We expressed the human wild-type and mutated G6PD gene in yeast Saccharomyces cerevisiae which allowed the characterization of the Suwalki variant. We showed that human wild-type, as well as the mutated (1226 C→G) G6PD gene, functionally complemented the phenotype displayed by the yeast strain with disruption of the ZWF1 gene (homologue of the human G6PD gene). Comparison of wild-type (wt) human G6PD purified from yeast and from blood shows no significant differences in the K m values for G6P and in the utilization rate for the substrate analogue, 2-deoxyG6P. The P409R substitution leads to drastic changes in G6PD kinetics. The specific activity as well as stability of mutated G6PD is also significantly reduced. Besides this, the effect of this mutation was analyzed using a model of the tertiary structure of the human enzyme. The localization of the P409R mutation suggests that it may influence the stability of the whole protein by changing tetramer interactions and disturbing the binding of structural NADP +.